2018
DOI: 10.1007/s00268-018-4727-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Postoperative Pneumonia Developing After Discharge on Long‐Term Follow‐up for Resected Lung Cancer

Abstract: Our findings revealed a high incidence and mortality of PDAD among patients who had undergone lung resection with long-term follow-up. Therefore, PDAD could be associated with poorer overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 47 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Cancer patients are at a higher risk of drug-drug interactions (DDIs), because they usually take multiple medications. Moreover, the majority of cancer patients are elderly individuals who require additional medications due to comorbidities (Riechelmann et al, 2007;Targownik et al, 2007;Shinohara et al, 2018;Herrmann, 2020). Studies have shown that 0.6-5% of hospitalizations related to adverse drug events (ADEs) are because of drug interactions, which is generally believed to account for a significant proportion of ADEs (Becker et al, 2007;Roughead et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer patients are at a higher risk of drug-drug interactions (DDIs), because they usually take multiple medications. Moreover, the majority of cancer patients are elderly individuals who require additional medications due to comorbidities (Riechelmann et al, 2007;Targownik et al, 2007;Shinohara et al, 2018;Herrmann, 2020). Studies have shown that 0.6-5% of hospitalizations related to adverse drug events (ADEs) are because of drug interactions, which is generally believed to account for a significant proportion of ADEs (Becker et al, 2007;Roughead et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in patients with advanced lung cancer who have had lung resection, CAP is a serious and often lifethreatening condition. [6][7][8] The rate of postoperative bacterial pneumonias remains high and may confer an increased risk of metastasis. 9 During the initial management of a patient with CAP, it is crucial to identify possible risk factors and empirical antimicrobial treatments, as the causative pathogen is unknown.…”
Section: Introductionmentioning
confidence: 99%